The Preparation of Hollow Mesoporous Bioglass Nanoparticles With Excellent Drug Delivery Capacity for Bone Tissue Regeneration - Wang, Yudong; Pan, Haobo; Chen, Xiaofeng (Frontiers in Chemistry, 2019)
In this work, hollow mesoporous bioglass (HMBG) nanoparticles were prepared in a hexadecyl trimethyl ammonium bromide (CTAB)-cyclonexane-ethanol-water (O/W) emulsion system. The HMBG nanoparticles possessed higher drug storage ability and stable drug release behavior which resulted from HMBG’s unique mesoporous structure. The mesoporous structure could be modulated by adjusting concentration of CTAB. The specific surface area and drug loading efficiency was as high as 749.619 m2g-1 and 55.1%. Besides, in vivo experiments demonstrated that the HMBG nanoparticles could promote the bone tissue regeneration and the drug-loading HMBG nanoparticles possessed better repair capability. The unique structure and properties might make the HMBG nanoparticles good candidates as drug carriers and repair materials for bone tissue regeneration.